miR-15a-5p up-regulates TLR4 and induces the formation of hypertrophic scars and keloids: miR-15a-5p promotes hypertrophic scar and keloid formation - Pang, Junyao; Zhu, Lijiao; Lv, Yongquan; Xu, Lianlian; Li, Ningxi; Guo, Ping; Feng, Qiuyuan (Cellular and Molecular Biology, 2023)
The formation of hypertrophic scar and keloid is considered to be a very complex pathological process. Our previous studies have shown that miR-15a-5p is an important miRNA in HTS tissues, and its expression level is significantly increased. Therefore, the potential mechanism of action of miR-15a-5p in scarring arouses our interest. This study preliminarily investigated the expression level of miR-15a-5p in HTS tissue and normal skin tissue and further explored the molecular mechanism. The results of this study once again confirmed that the expression level of miR-15a-5p was increased in HTS tissues and cells, and the closely related mRNA and protein levels of MyD88 and TGF-β were also highly expressed. The relative expression levels of fibrosis-related indicators in HTsFb cells were up-regulated, such as collagen-Ⅰ, collagen-III and α-SMA. We constructed the HTS cell model and BALB/c nude animal model, and down-regulating miR-15a-5p, the HTsFb cells proliferation was inhibited, and qRT-PCR results showed that the fibrosis index mRNA was also reduced, and significantly reduce the pathological state of scar tissue. In conclusion, miR-15a-5p may participate in the formation and development of HTS through TLR/MyD88 signaling pathway and TGF-β1 signaling pathway.